The Social Construction of Religious Moderation among Madurese Kiai: A Multi-Site Study of Indonesian Pesantren - Busahwi; Umi Sumbulah; Samsul Susilawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Indonesia’s pesantren have long been regarded as institutional centers of Islamic moderation. However, the socio-pedagogical processes through which religious moderation is constructed, transmitted, and internalized remain theoretically underexplored. This study examines how Madurese kiai construct and implement religious moderation across different pesantren typologies in Madura, Indonesia. Using a qualitative multi-site case study approach, data were collected through in-depth interviews, participant observation, and document analysis at three pesantren during 2025. The findings reveal that all sites share a common wasathiyyah theological foundation based on tawassuth, tasamuh, tawazun, and ta’adul, while differing in their institutional implementation. Al-Hikam integrates moderation into the formal curriculum, Assirojiyyah embeds it through contextual kitab kuning interpretation within the salaf tradition, and Nurul Hikmah promotes it through dialogic-participatory pedagogy. Applying Berger and Luckmann’s framework of externalization, objectivation, and internalization, the study demonstrates that religious moderation in pesantren is not merely a state-driven normative agenda but a socially constructed reality shaped through kiai authority, pedagogical traditions, and everyday institutional interaction. The study contributes to the growing scholarship on Islamic education by conceptualizing religious moderation as a dynamic socio-cultural construction rather than solely a curricular project.